Using bioinformatics technology to mine the expression of serum exosomal miRNA in patients with traumatic brain injury - Huang, Xintao; Xu, Xinjuan; Wang, Ce; Wang, Yi; Yang, Yajun; Yao, Tianle; Bai, Rui; Pei, Xile; Bai, Feirong; Li, Panpan (Frontiers in Neuroscience, 2023)
Traumatic Brain Injury (TBI) is considered to be the most common traumatic disease among neurological diseases, usually with high mortality and long-time complications, which is always a global public health issue. To date, there are few progresses in the research on serum markers for TBI. Therefore, it is urgently needed for biomarkers that can function sufficiently in the TBI diagnosis and evaluation. Exosomal microRNA(miR), a stable circulating marker in serum, has aroused widespread interest among researchers. To explore the level of serum exosomal miR after TBI, we detected the miRs expression in serum exosomes extracted from 14 TBI patients with next-generation sequencing (NGS), and explored the potential biomarkers for TBI with bioinformatics screening. Compared with the control group, there were 245 miRs (136 for up-regulated and 109 for down-regulated) in the serum of the TBI group changed significantly.We found serum exosomal miR expression profiles associated with neurovascular remodeling, the integrity of the blood-brain barrier, neuroinflammation, and a cascade of secondary injury, including 8 upregulated has-miR (has-miR-124-3p, has-miR-137-3p, has-miR-9-3p, has-miR-133a-5p, has-miR-204-3p, has-miR-519a-5p, has-miR-4732-5p, has-miR-206) and 2 downregulated miR (has-miR-21-3p、has-miR-199a-5). The results revealed that serum exosomal miR may become a new research direction and breakthrough for the diagnosis and pathophysiological research of TBI patients.